2019
DOI: 10.3390/met9030344
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Rate-Dependent Deformation Behavior and Mechanical Properties of a Multi-Phase Medium-Manganese Steel

Abstract: The strain-rate-dependent deformation behavior of an intercritically annealed X6MnAl12-3 medium-manganese steel was analyzed with respect to the mechanical properties, activation of deformation-induced martensitic phase transformation, and strain localization behavior. Intercritical annealing at 675 °C for 2 h led to an ultrafine-grained multi-phase microstructure with 45% of mostly equiaxed, recrystallized austenite and 55% ferrite or recovered, lamellar martensite. In-situ digital image correlation methods d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…However, PLC bands observed as serrations on tensile curves appear less regularly when compared to Lüders bands. The presence of Lüders and PLC bands was observed by Wang et al [13] and Sevsek [47] in cold-rolled and intercritically-annealed 7Mn-0.14C-0.23Si and X6MnAl12-3 steels, respectively. Callahan et al [40] reported that the temperature of intercritical annealing affects the occurrence of PLC and Lüders bands.…”
Section: Cold-rolled Medium-mn Steelsmentioning
confidence: 71%
See 1 more Smart Citation
“…However, PLC bands observed as serrations on tensile curves appear less regularly when compared to Lüders bands. The presence of Lüders and PLC bands was observed by Wang et al [13] and Sevsek [47] in cold-rolled and intercritically-annealed 7Mn-0.14C-0.23Si and X6MnAl12-3 steels, respectively. Callahan et al [40] reported that the temperature of intercritical annealing affects the occurrence of PLC and Lüders bands.…”
Section: Cold-rolled Medium-mn Steelsmentioning
confidence: 71%
“…The effect of strain rate in medium-and high-Mn steels is usually discussed in terms of negative strain rate sensitivity (NSRS), which reduces the amount of work hardening at high strain rates [47,[51][52][53]. Usually, conventional TRIP steels do not show this effect [48].…”
Section: Effect Of Strain Rate On the Plc Effectmentioning
confidence: 99%
“…Engineering stress-strain curves of HMnS with various SFE/activated deformation mechanisms and the X30MnAl23-1 HMnS subjected to different processing techniques. MMnSmedium-manganese steel [42], SRIP-slip-band refinement-induced plasticity [43], TRIPtransformation-induced plasticity, TWIP-twinning-induced plasticity [44], ECAP-equal-channel angular pressing [45], SLM-selective laser melting [46]. Figure 8.…”
Section: Mechanism-oriented Alloy Designmentioning
confidence: 99%
“…Engineering stress-strain curves of HMnS with various SFE/activated deformation mechanisms and the X30MnAl23-1 HMnS subjected to different processing techniques. MMnS-medium-manganese steel [42], SRIP-slip-band refinement-induced plasticity [43], TRIP-transformation-induced plasticity, TWIP-twinning-induced plasticity [44], ECAP-equal-channel angular pressing [45], SLM-selective laser melting [46]. Indeed, several of the approaches presented in Figure 8 have already been transferred to HEAs, such as TRIP and TWIP effects [17,47], precipitation hardening in compositionally complex alloys (CCAs) [48], recovery annealing [8], severe plastic deformation [49], additive manufacturing [50], etc.…”
Section: Mechanism-oriented Alloy Designmentioning
confidence: 99%
“…Most papers using the ART effect deal with applications for sheet products, as the necessary heat treatment can be best tailored by continuous strip annealing treatments. Thus, the composition requirement and the process parameters have been studied for a wide range of medium manganese steels [17][18][19][20]. As the time-temperature profiles of sheet products cannot be applied on forging parts because of the complex geometries and great cross sections, only simple and robust heat treatments can be used to modify the microstructure.…”
Section: Introductionmentioning
confidence: 99%